Implementation of an Overheat Monitoring and Protection System for Community Empowerment Programs Using Thermocouples - Akhmad Azhar Firdaus; Rama Arya Sobhita; Anggara Trisna Nugraha (Politeknik Perkapalan Negeri Surabaya, 2025)
Induction motors, which operate continuously, such as those used in power plant cooling systems, are at risk of failure that can result in significant losses, such as power outages when the turbine halts due to overheating. Therefore, it is crucial to have a system that monitors the temperature of the induction motor to detect potential overheating and facilitate maintenance. This study aims to design and test a temperature monitoring system for induction motors using thermocouple sensors connected to an LCD display. The methodology begins by identifying issues related to motors running non-stop, followed by a review of relevant literature and system design. Once the system was built, testing was conducted by heating the probe and measuring the temperature with a thermometer to compare the readings with those from the thermocouple sensor. The test results showed that the system accurately displayed the temperature on the LCD, with an error margin that was calculated to evaluate the sensor's accuracy. Based on these results, it can be concluded that the temperature monitoring system functions well and can be used as a reliable overheat detection system for induction motors. This system is expected to simplify maintenance processes and reduce the risk of motor damage caused by overheating. Additionally, the integration of this technology in community-based power plant initiatives could enhance the sustainability and safety of rural energy projects, ensuring a more reliable power supply for community empowerment programs.